First case of a vermiform appendix duplication type A volvulus: A very rare cause of acute abdomen - Gustavo H. Peniche González; Antonio F. Medina Vega; Celso T. Corcuera Delgado; Luis A. Chávez Talamantes; Claudia N. Alemán Sánchez (Elsevier, 2015)
The duplication of the vermiform appendix is a rare anatomical variant. Most of the cases reported with symptomatology of appendicitis and the finding of a duplication of vermiform appendix. A seven year old female, with abdominal septic shock, plain abdominal radiography with distended transverse intestinal loop with air-fluid levels and absence of air in distal colon and rectal ampula. Emergency laparotomy was performed finding a blind loop with secondary necrosis volvulus, with the torsion being at the base of the duplication, connected at the middle portion of the vermiform appendix; desvolvulus and resection was performed in a block fashion with Parker-Kerr technique using a 4-0 polyglactin suture. There are 100 cases of duplication of appendix reported worldwide. In our case, a duplication of the vermiform appendix type A was presented, shown by the surgical findings and corroborated by pathology samples of intestinal tissue featuring smooth muscle tissue and transmural necrosis and fibrinopurulent exudate in serous.